2013
DOI: 10.1007/jhep06(2013)089
|View full text |Cite
|
Sign up to set email alerts
|

Moduli stabilization and the holographic RG for AdS and dS

Abstract: We relate moduli stabilization (V ′ = 0) in the bulk of AdS D or dS D to basic properties of the Wilsonian effective action in the holographic dual theory on dS D−1 : the single-trace terms in the action have vanishing beta functions, and higher-trace couplings are determined purely from lower-trace ones. In the de Sitter case, this encodes the maximal symmetry of the bulk spacetime in a quantity which is accessible within an observer patch. Along the way, we clarify the role of counterterms, constraints, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The reason is that various aspects of the holographic RG simplify in the Hamiltonian approach, as found in [42][43][44], and more recently in [45][46][47]. 5…”
Section: Hamiltonian Formulationmentioning
confidence: 99%
“…The reason is that various aspects of the holographic RG simplify in the Hamiltonian approach, as found in [42][43][44], and more recently in [45][46][47]. 5…”
Section: Hamiltonian Formulationmentioning
confidence: 99%
“…This would generically not produce the same sharp agreement, but there may be special flows that also fit the facts. In [28], we found that if one treats one side, e.g. w < w uv in dS d+1 , as the gravity dual of a matter theory, this theory has a highly constrained holographic Wilsonian RG flow: single-trace operators do not flow, and higher traces are determined in terms of lower ones.…”
Section: Jhep07(2018)050mentioning
confidence: 99%
“…One aspect of this is that the dual matter sectors only behave as a pair of CFTs at sufficiently low energies; they are deformed by irrelevant operators. 4 3 dS d+1 is a very special Randall-Sundrum [27] system, with no explicit Planck brane and a highly constrained holographic RG flow [28]. The d-dimensional gravity is dynamical at finite times, and we will be concerned with the period over which the spacetime is classically de Sitter.…”
Section: Jhep07(2018)050 2 Setupmentioning
confidence: 99%
See 2 more Smart Citations